Autophagy modulates the Mycobacterium tuberculosis-induced cytokine response - Kleinnijenhuis, Johanneke (Blackwell Science Inc, 2011)
Both autophagy and pro-inflammatory cytokines are involved in the host defence against mycobacteria, but little is known regarding the effect of autophagy on Mycobacterium tuberculosis (MTB)-induced cytokine production. In the present study, we assessed the effect of autophagy on production of monocyte-derived and T-cell-derived cytokines, and examined whether two functional polymorphisms in autophagy genes led to altered cytokine production. Blocking autophagy inhibited tumour necrosis factor-α (TNF-α) production, while enhancing interleukin-1β (IL-1β) production in peripheral blood mononuclear cells stimulated with MTB. Induction of autophagy by starvation or interferon-γ (IFN-γ) had the opposite effect. The modulation of both TNF-α and IL-1β production by autophagy was induced at the level of gene transcription. Functional polymorphisms in the autophagy genes ATG16L1 and IRGM did not have a major impact on MTB-induced cytokine production in healthy volunteers, although a moderate effect was observed on IFN-γ production by the ATG16L1 T300A polymorphism. These data demonstrate the interplay between autophagy and inflammation during host defence against mycobacteria, and future studies to investigate the clinical implications of these effects for the susceptibility to tuberculosis are warranted.